Existing is Ordinary: resistance maps in the curricula and teaching - Alexandra Garcia; Allan de Carvalho Rodrigues (Universidade Federal do Rio Grande do Sul, 2019)
Faced nowadays with the words teaching, curriculum and school, the verb to resist sounds like an inescapable premise to the possibilities of fairer, more solidary and democratic social forms. Based on results from researches on the production of curricula and teachers training, we seek, through teacher narratives, to map resistance movements of the public and the common in everyday practices. We argue that forms of resistance do not necessarily arise as responses to hegemonic logics and to agendas that reduce life to economic interests. To resist, in the dialogue that we establish with authors from the field of philosophy, of the new epistemologies and of the studies of everyday life, implies in the ordinary and everyday production of the forms of existence.